KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGEMBANGKAN BUDAYA SEKOLAH MELALUI MANAJEMEN BERBASIS SEKOLAH (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2018)
This research investigated headmaster’s strategy to develop school’ culture through School Based Management. It used a qualitative approach with case studies. Data were collected by using interviews, observation, and study of the documents/artifacts. Data validation was done through credibility, transferability, dependability, and confirmability. This results showed that headmaster’s strategy to develop school’ culture started from developing discipline culture.